ANALISIS KESANTUNAN BERBAHASA PADA TAJUK RENCANA HARIAN SUARA MERDEKA DAN RELEVANSINYA SEBAGAI BAHAN AJAR MENULIS TEKS EDITORIAL SISWA KELAS XII SMA - Putri, Mutiah Ariska; Saddhono, Kundharu; Waluyo, Budi (Universitas Sebelas Maret, 2020)
The purpose of this research are to describe and explain: (1) compliance with modesty and politeness infringement on editorial Suara Merdeka daily; (2) the function of politeness in Suara Merdeka daily editorials; (3) the relevance of politeness in Suara Merdeka daily editorial resource as text editorial writing class XII student in high school. This research is a qualitative descriptive by using content analysis method. The data used in this study of the document, namely Suara Merdeka daily editorial and informants. Technique intake of study subjects using purposive sampling. Data collection techniques used, namely the study of the content and interviews with informants. Test the validity of the data using triangulation theory and triangulation of data sources. Data were analyzed using flow model analysis techniques Miles and Huberman. The result show that (1) compliance politeness of the most prevalent is the sympathy maxim, while the least was found is the maxim of simplicity. On offense politeness most common is the maxim of the award, while the least was found is the maxim of agreement; (2) the function of politeness most common is the function stated, while that is not found at all is a function of apology; (3) analysis of politeness in Suara Merdeka daily editorial relevant if used as teaching material writing editorial texts for 12th grade students of senior high school.